Effects of a high protein intake on kidney function and acid excretion in bodybuilders - Abdullah, Tahseen Abdah; Othman, Hawzheen Kareem (International Journal of Psychosocial Rehabilitation, 2020)
Body builder often prefer a high protein diet to achieve maximum skeletal muscle hypertrophy. In this study the effect of high protein diet on renal function test and urine pH was studied. The renal deteriorate activity of the high protein intake was determined by assessing biochemical parameters. Serum creatinine and urea were significantly elevated in bodybuilders with high protein intake While, the urine pH was decreased significantly compared with control group.